Deployment of Aziridines for the Synthesis of Alkaloids and Their Derivatives - Macha, Lingamurthy; D’hooghe, Matthias; Ha, Hyun-Joon (Synthesis, 2019)
Various (activated and non-activated) aziridines with diverse substitution patterns have been deployed successfully as starting materials for the synthesis of a wide variety of alkaloids via suitable functionalization and aziridine ring transformation. Alternatively, the preparation and interception of reactive aziridine intermediates has also been shown to constitute a valid approach toward alkaloid synthesis. This review summarizes aziridine-mediated syntheses of alkaloids, in which the aziridine is mobilized as either a substrate or an advanced synthetic intermediate.1 Introduction2 Alkaloids Synthesis from Aziridine Starting Materials2.1 (2R)- and (2S)-Hydroxymethyl-N-(1-phenylethyl)aziridines2.2 N-Benzylaziridine-2-carboxylates2.3 2-Substituted N-Tosyl- or N-Tritylaziridines2.4 2,3-Disubstituted N-Cbz- or N-Tosylaziridines2.5 N-DMB-aziridines3 Alkaloids Synthesis from Aziridines as Key Advanced Synthetic Intermediates3.1 Alkylative Aziridine Ring Opening3.2 Arylative Aziridine Ring Opening3.3 Ring Expansion3.4 Oxidative Aziridine Ring Opening3.5 Heteroatomic Nucleophilic Aziridine Ring Opening3.6 Reductive Aziridine Ring Opening4 Conclusion
Keywords: aziridine; ring strain; iminosugars; alkaloids; natural products